U.S. wage-price dynamics, before, during and after COVID-19, through the lens of an empirical econometric model - Gunnar Bårdsen; Ragnar Nymoen (University of Oslo, Department of Economics, 2024)
We specify an empirical model of US inflation which has the dynamics of wage and price setting at its core. In the dynamic wage equation an equilibrium-correction term connects the wage level to industrial prosperity indicators. In that way, the role of wage setting in the dynamics of the functional income distribution and in the rent-sharing processes becomes clearer than with a wage Phillips curve. At the same time, it does not exclude such explanatory variables that are typically found in empirical U.S. wage Phillips curves: changes in costs-of-living and indicators of labour market tightness, On the price side of the wage-price spiral, the empirical model includes an import price index and the price of oil. Existing studies of pandemic-era inflation have confirmed that shocks to energy prices were important, but have not included imported inflation more broadly. Estimation and simulation results indicate that wage growth was strongly affected early in the pandemic, but without breaking the long-run mean of wage growth. The strong rise in the price index of private consumption expenditure that started in 2021 therefore had a background in an increased wage level, but was dependent on other factors to evolve as it did: Namely a strong and broad increase in international prices, and in energy prices in particular.
Keywords: C32; C53; C54; E17; E27; E32; E37; E65; 330; Inflation; Coronavirus; Empirical method; Wage level; Price level; Functional income distribution; Phillips curve; USA; Inflation; Coronavirus; Empirische Methode; Lohnniveau; Preisniveau; Funktionelle Einkommensverteilung; Phillips-Kurve; USA